Job satisfaction of healthcare professionals in palliative care departments and factors affecting job satisfaction during the COVID-19 pandemic - Sinanović, Šćepan; Kilibarda, Tatjana; Bubanj, Saša; Prodović, Tanja; Potić, Srećko; Sekulić, Jelena; Spasić, Marko; Subotić, Slobodan; Kostić, Marina; Petrović, Marko; Popović Ilić, Tatjana; Tomović, Milena; et al. (Vojnosanitetski pregled, 2024)
Background/Aim. The COVID-19 pandemic had a significant impact on the healthcare system, particularly healthcare providers such as nurses/medical technicians, who were obliged to adhere to strict procedures and manage their time effectively during shifts. The aim of this study was to identify internal strengths, weaknesses, threats, and challenges in palliative care management during the COVID-19 pandemic from the perspective of nurses/medical technicians. Methods. A cross-sectional study was conducted on a 100% sample of nurses/medical technicians working in hospital-based palliative care in two clinics in Belgrade (47 respondents in total). The research instrument was a Questionnaire on Employee Satisfaction. The survey was conducted during September and October 2022. Results. Assessing the job satisfaction of nurses/ medical technicians revealed moderate job satisfaction (3.43), which was mostly influenced by appropriate financial compensation and the implementation of measures to prevent and control the spread of the COVID-19 infection. The dimensions of management that were significantly related to respondents’ satisfaction were motivation and adequacy of hygienic conditions and measures to control COVID-19 (χ2 = 62.83, p = 0.004 and χ2 = 36.42, p = 0.006, respectively). Conclusion. Nurses/medical technicians who experience stress at work in regular conditions tend to react the same way in different conditions, such as those related to COVID-19 infection. The most difficult challenge that the management faces is the recognition of the importance of the work of nurses/medical technicians by the community. Therefore, it is vital to respect and support the most important professional values of nurses/medical technicians, such as valuable achievements, the importance of professional challenges, personal growth and development, and independence in practice.